Seasonal and circadian study of the essential oil of Myrcia sylvatica (G. Mey) DC., a valuable aromatic species occurring in the Lower Amazon River region. (August 2018) - Raposo, Juliana Divina A.; Figueiredo, Pablo Luis B.; Santana, Rosiele L.; da Silva Junior, Antonio Q.; Suemitsu, Chieno; da Silva, Rodrigo; Mourão, Rosa Helena V.; Maia, José Guilherme S.
Abstract: Myrcia sylvatica (G. Mey.) DC., Myrtaceae, is an aromatic species that occurs in savanna areas of the Lower Amazon River, Brazil. Its essential oil showed an excellent yield, presenting a moss green coloration and a woody and spicy scent. The seasonal and circadian study of the leaf oils and the analysis of oil composition of the fruits were performed by GC and GC-MS. The primary compounds identified in fruit oil were δ-cadinene, β-selinene, 1- epi -cubenol, cubenol, α-calacorene, β-pinene, and trans -muurola-3, 5-diene. In the leaf oils, the main compounds found were β-selinene, 1- epi -cubenol, cadalene, mustakone, δ-cadinene, α-calacorene, trans -calamenene, cubenol and caryophyllene oxide. Analyses of PCA and HCA applied to the samples of leaf oils presented a quantitative variation in their compositions, attributed to the rainy and dry periods. Also, it was observed a significant influence on the volatile constituents of the oils in the rainy season, depending on the time of collection. Thus, it was confirmed that the seasonal variation in the oil composition from leaves of M. sylvatica should be due to the influence of the climatic parameters, during the plant collection. Graphical abstract: Highlights: The seasonal and circadian study was fundamental to contribute to chemotaxonomic of M. sylvatica . PCA and HCA analyses showed quantitative variation in the composition due the rainy and dry seasons. Significant variation on the oil constituents was observed in the rainy season and collection time. The seasonal variation in the oil composition is due to the influence of the climatic parameters.